The Art of Detecting Antibodies against Factor VIII - Tiede, Andreas; Alberio, Lorenzo (Hämostaseologie, 2020)
Antibodies against factor VIII (FVIII) can be detected based on their ability to neutralize the procoagulant activity of FVIII (neutralizing antibodies, inhibitors), or based on their specific binding capacity to FVIII protein. This article reviews the available assays and their clinical interpretation in patients with congenital and acquired hemophilia.
Keywords: coagulation; assay; inhibitor; autoantibodies; Bethesda assay